Heterogeneous presence of myofibroblasts in hereditary gingival fibromatosis - Carolina C. Bitu (journal of clinical periodontology, 2006)
Background/Aim: Hereditary gingival fibromatosis (HGF) fibroblasts are characterized by an increased production of collagen and transforming growth factorb1 (TGF-b1), resulting in a fibrotic enlargement of the gingiva of affected patients. A common feature of interstitial fibrosis is the occurrence of myofibroblasts, which are regarded as the predominant cells in matrix synthesis. The goal of this article is to describe the presence of myofibroblasts in HGF in order to elucidate the mechanisms underlying HGF gingival overgrowth. Materials and Methods: Fibroblast cell lines and gingival samples from patients of two distinct families affected by HGF and from normal gingiva (NG) were included in this study. To characterize the presence of myofibroblasts, the expression of specific myofibroblast marker smooth muscle isoform of a-actin (a-SMA) was examined by semi-quantitative reverse transcriptase-polymerase chain reaction (RT-PCR), Western blot, immunofluorescence, and flow cytometric analysis. Immunohistochemistry against the a-SMA antigen was performed in the gingival tissue samples. Results: Our results demonstrated a significant increase in the expression of the myo- fibroblast marker a-SMA in cells from one HGF family (designed as HGF Family 2), which are also characterized by an elevated expression of type I collagen, TGF-b1 and connective tissue growth factor (CTGF). Additionally, a-SMA-positive cells were broadly detected in the gingival tissue samples from HGF Family 2 patients. In contrast, a-SMA expression by HGF Family 1 cells was quite similar to NG cells and no myofibroblasts were detected immunohistochemically, despite the higher levels of TGF-b1 and type I collagen in HGF Family 1 fibroblasts than in NG cells. The expression of CTGF, which has been considered a key molecule to promote the transdifferentiation of myofibroblasts via TGF-b1 activation, by HGF Family 1 cultures was significantly lower compared with HGF Family 2 and similar to NG control cells. Conclusions: Our results suggest that the presence of myofibroblasts in HGF could be dependent on CTFG expression levels, and different biological mechanisms may account for the gingival overgrowth observed in HGF patients. This could be an underlying reason for the high variable clinical expressivity of disease.